Electromagnetic Torque Analysis of SRM 12/8 by Rotor/Stator Pole Angle - Minh, D. B.; Hai, L. D.; Anh, T. L.; Quoc, V. D. (Engineering, Technology & Applied Science Research, 2021)
This paper presents the harmonic torque reduction by the different rotor pole angles of a three-phase 12/8 switched reluctance motor via an analytical model and simulation method. Improving torque performance by stator and rotor angles was applied for three-phase switched reluctance motor at stator pole/rotor pole ratios of 6/4, 8/12, 18/12, and 24/18. The average torque and the torque ripple effect by stator and rotor pole embrace have been recently studied in many projects. Due to the fact that leakage flux, flux density, and inductance are affected by the stator and rotor pole angles non-linear and linear leakage flux curves occur. Many stator and rotor pole angle combinations for the three-phase switched reluctance motor have already been done via a finite element method. In this paper, turn-on and turn-off angles will be figured based on stator and rotor pole embraces.